Acute Hepatitis B in a patient previously positive for antibody to surface antigen (anti-HBs) determined by radioimmunoassay: case report and review of the literature - Strauss, Edna; Sáez-Alquézar, Amadeo; Takeda, Augusta; Silva, Luiz Caetano da (Revista do Instituto de Medicina Tropical de São Paulo, 1985)
The determination of anti-HBs as a screening test before vaccination has been advisable in order to encounter immune individuals that don't need to receive vaccine protection. A case-report is presented and three other cases are reviewed from the literature. Anti-HBs was positive in these health-care personnels that developped typical acute B hepatitis. Different subtyping involving the d/y determinants were found in the first case, but false-positive anti-HBs even with high titres, determined by RIA, were found in the other cases. Concomitant determination of anti-HBc or absence of screening tests seem to be more reasonable policies until a low-cost and risk-free vaccine is produced.